(3cJGH cQGA GdOhQ hGdCHjVjf hcQGA GdQhGMd hGdOhGHs - (3CHh GdbGSe Hf edcs
(3ChdgG (B:s
(3bGd SMfhf CNHQfi CHh GdbGSe bGd SeYJ eGdckG jbhd ef JcGO CQVkG KdGK Sfjf HRQYgG ahRY ajgG SfI Ch SfJjf s
(3BNQgG (B:s
(3jfJgi HcJGH ZQS QShd Gddg Udi Gddg Ydjg hSde s
(3ef GdeSJNQLI eeG GSJNQLg eMeO Hf CMeO Hf GdYJjHi aeG djS ai GdeQhfI Ydi HYO bOjes
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(612/1) s
Keywords: (3Gdabg GdESdGejs